2015
DOI: 10.1021/jacs.5b03973
|View full text |Cite
|
Sign up to set email alerts
|

Modular Design of Self-Assembling Peptide-Based Nanotubes

Abstract: An ability to design peptide-based nanotubes (PNTs) rationally with defined and mutable internal channels would advance understanding of peptide self-assembly, and present new biomaterials for nanotechnology and medicine. PNTs have been made from Fmoc dipeptides, cyclic peptides, and lock-washer helical bundles. Here we show that blunt-ended α-helical barrelsi.e., pre-assembled bundles of α-helices with central channels-can be used as building blocks for PNTs. This approach is general and systematic, and uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
187
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 141 publications
(193 citation statements)
references
References 38 publications
2
187
0
4
Order By: Relevance
“…In these cases, the inner diameter can be tailored via the ring size of the peptide 2. The modular approach that we present to assemble PNTs from αHBs allows similar control mechanisms 7a. We have shown that the inner diameter varies with the oligomer state of the αHB, allowing PNTs with channels of 5–7 Å to be achieved.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…In these cases, the inner diameter can be tailored via the ring size of the peptide 2. The modular approach that we present to assemble PNTs from αHBs allows similar control mechanisms 7a. We have shown that the inner diameter varies with the oligomer state of the αHB, allowing PNTs with channels of 5–7 Å to be achieved.…”
mentioning
confidence: 91%
“…Our designs carry certain advantages, principally modularity and generality. Therefore, the control mechanisms that we describe should be readily transferrable to other αHB building blocks of varying pore size 7a,7c. The inner lumens of these barrels are also mutable,7b, 10 which should facilitate further the design of functional PNTs.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The overall goal of the paper is to investigate whether the use of standard bioinformatics algorithms is applicable for efficient and accurate structure-function modeling of the synthetic proteins subsets Hecht_α and Hecht_β. The applicability of the presented methodology will be discussed considering de novo protein subsets recently reported by Woolfson and co-workers [4,5,[23][24][25] and Baker and co-workers [1,26].…”
Section: Introductionmentioning
confidence: 99%